Disaster law - Lauta, Kristian Cedervall (Routledge, 2014)
"Over the last thirty years, the registered number of global disasters has more than quadrupled, and as a result all around the globe disasters and their management are today central to public and political agendas. Our conception of disasters, in particular natural disasters, has also changed significantly over the last 250 years. Disasters have changed from being understood as acts of God and Nature to today being understood through our own inability to avoid them. Natural disasters are increasingly analysed as social vulnerability exposed by natural hazards, rather than through hazards themselves (heavy rain, hurricanes or earthquakes). A disaster following an earthquake is therefore no longer seen as caused exclusively by tremors, but by poor building standards, ineffective response systems, or miscommunications. This book argues that this change could be seen as a social turn in our understanding of disasters which affects how we speak of, how we manage and how we feel before, during and after a disaster and affects our fundamental notions of duty, responsibility and justice.The book considers the role of law in disasters and in particular the regulation of disaster response and the allocation of responsibility in the aftermath of disasters. It argues that while traditionally law has approached emergencies, including natural disasters, from a dichotomy of normalcy and emergency. When a disaster occurred, a state of emergency was declared. In the state of emergency norms were replaced by exceptions; democracy by dictatorship; and rights by necessity. However, as the disaster becomes socialized the idea of a clear distinction between normalcy and emergency crumbles. Looking at international and domestic legislation from a range of jurisdictions the book shows how natural disasters are increasingly normalized and therefore increasingly objects of legal regulation and interpretation and the impact this has had on disaster law"..